The Effect of Patient-Centered Care-Based Services on Patient Behavioral Intentions with Trust as A Mediating Variable at Dr Moewardi Hospital, Surakarta City - Giffa Sastha Audrey Mellani; Rohendi Rohendi; Yani Restiani Widjaja (CV. Civiliza Publishing, 2026)
This study aims to determine the direct influence of patient-centered Care on patient behavioral intentions, the direct influence of patient-centered Care on patient trust, the direct influence of patient trust on patient behavioral intentions, and the role of patient trust as a mediating variable in the relationship between patient-centered Care and patient behavioral intentions at Dr. Moewardi Surakarta Hospital. The research method uses a quantitative correlational approach. Data were collected through questionnaires to outpatients and inpatients of Dr. Moewardi Surakarta Hospital and analyzed using statistical tests to test the direct influence and role of mediation. The results of the study show that Patient-centered Care has a direct positive effect on patient behavioral intentions and patient trust at Dr. Moewardi Surakarta Hospital. Patient trust also has a direct positive influence on the patient's behavioral intentions, which is reflected in the patient's increased tendency to make repeat visits and make recommendations. Patient trust has been proven to mediate the influence of patient-centered Care on patient behavioral intentions, so that patient-oriented services not only have a direct impact on behavioral intentions, but are also strengthened through the formation of trust. These findings show that consistent implementation of patient-centered Care plays a role in building patient trust and encouraging positive behavioral intentions towards hospital services.